Does Heuristic Bias Matter for Long and Short-Term Investment Decision-Making During the COVID-19 Pandemic? - Wahyu Febri Ramadhan Sudirman; Muhammad Ikhsan Alif; Anggun Pratiwi (Faculty of Economics and Business, Universitas Gadjah Mada, 2023)
Introduction/Main Objectives: This study examines the effect of heuristic behavior on investment decision-making in the long- and short-term during the COVID-19 pandemic in the Indonesian capital market. Background Problems: Traditional finance cannot fully explain how investors behave in the capital market. Investors will tend to use heuristics when making investment decisions because humans have cognitive limitations, as explained in the bounded rationality theory. Especially during the COVID-19 pandemic, investors have shown their irrationality due to the high uncertainty and panic caused by the COVID-19 pandemic. This phenomenon can only be explained by behavioral finance. Novelty: This study examines the effect of bias on the investment decision-making of investors who make long-term and short-term investments. Previous studies only tested the impact of bias directly, without differentiating the length of time of the investment. Research Methods: This study used partial least squares structural equation modelling (PLS-SEM) with WarpPLS tool. Testing the moderating effect was undertaken using multi-group analysis (MGA). Finding/ Results: The results of this study indicate that anchoring and availability bias have a positive effect on investment decision-making, while representativeness bias has no significant impact. Investment time moderates the effect of representativeness bias on irrational investment decision-making, while anchoring and availability bias are not supported. Conclusion: Anchoring and availability heuristics will increase irrational investment decisions, while the effect of representativeness heuristics on irrational investment decisions will decrease when investors make long-term investments.